The effect of deprivation on the incidence of mandibular fractures in a British city. Issue 2 (April 2017) - Wilson, M.H.; Robinson, J.P.; Sisson, R.T.; Revington, P.J.; Thomas, S.J.
Abstract: Aim: To examine the relationship between social and material deprivation and mandibular fractures. Method: Three hundred and forty three consecutive patients who underwent mandibular fracture fixation were selected for the study. After exclusions, 290 were divided into age groups and ranked according to their Index of Multiple Deprivation (IMD) score. Rankings were determined using postcodes, and divided into quintiles for statistical analysis. Results: Ages ranged from 7 to 82 with 146 (50%) patients aged between 20 and 29. Males accounted for 85% of cases. The most common site of fracture was the angle (n = 195) and assault was shown to be the most common mechanism of injury (63.3%). A strong relationship was demonstrated between fractures of the mandible and worsening deprivation, with the most striking relationship seen with fractures sustained as a consequence of assault. Females were less likely than males to sustain a fracture of the mandible as a consequence of assault; however, when assault was the mechanism of injury they were also likely to be from a deprived background. Conclusion: This study has demonstrated that a strong relationship exists between deprivation and the incidence of mandibular fractures in our catchment area. Fractures that resulted from interpersonal violence were shown to have a particularly strong correlation with deprivation.